The predictive role of Systemic Inflammation Response Index (SIRI), Neutrophil-Lymphocyte Ratio (NLR), and Platelet-Lymphocyte Ratio (PLR) in the prognosis of acute coronary syndrome in a tertiary care hospital - Hamrish Kumar Rajakumar; Varsha Coimbatore Sathyabal; Mannar Vasanthan; Ramesh Dasarathan (Heliyon)
Background: & Objective: Acute coronary syndrome (ACS) is a major cause of mortality globally, with significant morbidity and economic impact. This study aimed to correlate the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic inflammatory response index (SIRI) values in ACS patients with their prognosis via the GRACE scoring criteria and to propose the SIRI as a superior inflammatory marker for predicting ACS prognosis. Methods: Ethical approval was obtained for a retrospective cross-sectional study, which included patients from the outpatient department and Tamilnadu Accident Emergency Initiative Ward at Government Medical College, Omandurar Government Estate, who were diagnosed with ACS according to American College of Cardiology guidelines from January 2022 to December 2023. We excluded patients with familial hypercholesterolemia, platelet disorders, infections, inflammatory conditions, or incomplete health records. Data on demographics, clinical findings, blood counts, ECGs, cardiac enzymes, echocardiography, serum creatinine, and vital signs were collected and analyzed to calculate the NLR, PLR, SIRI, and GRACE scores. Statistical analyses included Kolmogorov‒Smirnov and Anderson‒Darling tests, Spearman correlation, Kruskal‒Wallis one-way ANOVA, GLM modeling, k-fold cross-validation, and receiver operating characteristic (ROC) curve analysis. Results: After applying the exclusion criteria, 247 ACS patients were included in the analysis. Significant associations were found between the NLR and the PLR, SIRI, and GRACE scores. The SIRI demonstrated the strongest association, whereas the PLR had the weakest association. All three variables significantly influenced prognostic risk, as determined by the GRACE score. GLM models highlighted the predictive significance of the NLR, PLR, and SIRI in estimating GRACE scores, with the SIRI showing potential superiority. K-fold cross-validation confirmed the superior predictive accuracy and ability of the SIRI to explain a larger proportion of variance in GRACE scores than the NLR and PLR. Conclusions: The SIRI emerges as a promising prognostic marker for ACS, outperforming the NLR and PLR. Its ease of calculation from routine hemogram tests underscores its potential clinical utility for risk stratification in ACS management. Further validation and integration into existing risk assessment models could enhance prognosis assessment in ACS patients.